Generation of transformable spheroplasts from mycelia, macroconidia, microconidia and germinating ascospores of Neurospora crassa - J. C. Royer; C. T. Yamashiro (Fungal Genetics Reports, 1992)
For Neurospora to be generally useful in molecular studies it would be desirable to be able to prepare transformable spheroplasts from mycelia and any of the three types of spores produced by this organism. Transformable spheroplasts are currently prepared from germinating macroconidia by digestion with Novozym 234 in the presence of 1.0 M sorbitol (Vollmer and Yanofsky 1986. PNAS 83:4869-4873). This method is efficient, but requires a 3-5 hr germination step. Elimination of the germination step would be a technical advance. In addition, the standard method is usable only with strains that form large numbers of macroconidia. Thus, interesting mutants that are incapable of forming macro- conidia cannot be used as recipients in cloning experiments. A procedure for generating spheroplasts from mycelia of N. crassa has been reported (Buxton and Radford 1984. MGG 196:339-344). While large numbers of spheroplasts are released by this procedure, the frequency of transformation is low, and we have experienced difficulty obtaining repeatable results. Since we want to clone genes implicated in the macroconidiation process, we devised a procedure that improves the efficiency of transformation of mycelial spheroplasts. As an alternative approach, we developed an transformation protocol for microconidia. Since aconidial mutations can be introduced into a microcycle microconidiating background such as mcm (Maheshwari 1991. Exp. Mycol. 15:346-350), transformation of microconidia represents a viable option for the cloning of conidiation genes. A procedure for generating competent spheroplasts from germinating ascospores also was developed and provides an additional strategy for cloning conidiation genes.